Analysis of Corporate Social Responsibility Implementation And Social Audit at PT Semen Padang - Elvira Luthan; Sri Dewi Edmawati (International Conference On Law, Business and Governance (ICon-LBG), 2013)
The number of Corporate Social Responsibility (CSR) implementation in Indonesia is not so muchwhile the potential targets are very huge, such as environmental damage, unemployment, school drop-out,and poverty. One of its implementations that are common now is community development, which theemphases are on social and community capacity development. This study describes the implementation ofCSR and social audit in PT Semen Padang. PT Semen Padang as one of the largest states ownedenterprise in West Sumatra has a big hand in the development of West Sumatra.Analyses were performed with descriptive statistics and content analysis. Collecting data on the CSRactivities of PT Semen Padang was done by performing content analysis on the company's annual reportthat has been audited. Results of the analysis showed CSR’s model implementation in PT. Semen Padangis on the form of physical development such as public facilities, development of education, employmentempowerment, economic empowerment, community services, public health services, environmentalprotection, sports, and the arts. A pattern of implementation of CSR programs is generally done directlyand independently by a company-appointed team. PT Semen Padang has not implemented purely socialaudit of the implementation of the CSR report, but integrated in the audit of the company's annual report.